Answer:
The answer to this question can be defined as follows:
Explanation:
The given equation is:
![y_(k + 2) + 8y_(k +1) - 9y_(k) = 20k + 12..(1)](https://img.qammunity.org/2021/formulas/mathematics/high-school/v9qfthiwz5fn6kmpgg247sx70gg23zu6uf.png)
put,
![y_k = k^2\\\\y_(k+2)=(k+2)^2\\\\y_(k+1)=(k+1)^2\\\\](https://img.qammunity.org/2021/formulas/mathematics/high-school/yv28ejoo7zwmzvopbamarai9wcv516hcmx.png)
![(k+2)^2+8(K+1)^2-9k^2 = 20k+12\\\\=20k+12= 20K+12\\\\](https://img.qammunity.org/2021/formulas/mathematics/high-school/3u20iumagybiqj1tuuy92jpjd2g30tousc.png)
hence y_k=k^2 is its solution.
Now,
![\to y_(k+2)+ 8y_k + 1 - 9y_k = 20k + 12](https://img.qammunity.org/2021/formulas/mathematics/high-school/sbdkf1v2t2bur9dexgr9w5xy86ofxyt3ms.png)
the symbol form is:
![(E^2+8E-9)_(yk)=20k+12](https://img.qammunity.org/2021/formulas/mathematics/high-school/n2i0dcq73e27dco8zfu954c74kyqfz3n8s.png)
![\to m^2+8m-9=0\\\\\to m^2+(9-1)m-9=0\\\\\to m^2+9m-m-9=0\\\\\to m(m+9)-(m+9)=0\\\\\to (m+9)(m-1)=0\\\\\to m=-9 \ \ \ \ \ \ \ m=1\\](https://img.qammunity.org/2021/formulas/mathematics/high-school/5pdeh4mn5hsmqpjf8nqpy7va0toj7t9iwq.png)
The general solution is:
![y_k = c_1(-9)^k + c_2(`1)^k\\\\y_k =c_1(-9)^k+c_2](https://img.qammunity.org/2021/formulas/mathematics/high-school/hogblv438o9znw1sq3anai4zano2i9qakq.png)
The complete solution is:
![y_k=(y_k)_c+(y_k)_y\\\\y_k= c_1(-9)^k+c_2+k^2](https://img.qammunity.org/2021/formulas/mathematics/high-school/5tg2y3yix33rkqbhohmvk5musz80v2n47v.png)
The answer is option b:
![y_k = k^2 + c_1(-9)^k + c_2](https://img.qammunity.org/2021/formulas/mathematics/high-school/pygn4l4sv4l6u9gy4rmau4d7z4w0xb97t7.png)
After solve the complete solution is:
![\bold{y_1=c_1(-9)^k+c_2+k^2.....}](https://img.qammunity.org/2021/formulas/mathematics/high-school/69axmvqe1exm4pte1oswu3vjquw11w51ja.png)